Image Segmentation Markers in Diffusion Weighted Imaging (DWI) of MRCP Using Low and High B-Values for Diagnos-tic Assessment - Eva Maulidiana Hikmah; Leny Latifah; Luh Putu E. Santi M. (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Magnetic Resonance Cholangio Pancreatography (MRCP) is an important non-invasive imaging technique for the diagnosis of abnormalities in the biliary and pancreatic systems, including pancreatic mass and colletiasis. The use of an additional sequence of Diffusion Weighted Imaging (DWI) with b-value variations and image segmentation is thought to improve the accuracy of mass limit measurements on MRCP checks. This study aims to analyze the effect of b-value variation and image segmentation on the additional sequence of DWI in the MRCP examination of the accuracy of the mass limit measurement. The research used quantitative methods with MRCP image data capture equipped with a DWI sequence with b-value variations, using the matlab method. Image segmentation is performed to identify mass boundaries. Measurement accuracy is analyzed and compared between the variation in b-value and the segmentation techniques used. Research results show that variation of b-value 800 and image segmentation in additional DWI sequences have a significant effect on the improvement of accuracy of mass limit measurement on MRCP examinations. The b-value 800 variation is more optimal than the b-value 50 and the appropriate segmentation method can clarify the mass limit so that it supports a more accurate diagnosis. Sequence variations in b-value and image segmentation in the additional DWI sequences in MRCP examinations play an important role in improving the accuracy of mass limit measurements, which can aid in the diagnosis and management of diseases especially in lesion cases.